2019
DOI: 10.1016/j.ijid.2019.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the course of Brucella infection with qPCR-based detection

Abstract: To determine blood Brucella DNA loads between brucellosis patients and those without brucellosis. Methods: The patient group included 350 brucellosis patients. The control was composed of 200 subjects without brucellosis. The extracted DNA from blood was tested by quantitative polymerase chain reaction (qPCR). The cutoff value was determined by receiver operating characteristic curve analysis. A portion of the brucellosis patients were monitored by qPCR during therapy. Results: The detection limit of qPCR was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…This improved the sensitivity and specificity from the source of the detection method (Figure 1) [42]. Conventional nucleic acid amplification methods require at least 1 × 10 3 CFU/mL of colonies as a template to perform normal amplification [43,44], while sample enrichment by ICB in the ICB-LAMP-CRISPR/Cas12a method could reach a detection limit of 8 × 10 0 CFU/mL. For the captured C. jejuni, template DNA was released by direct heating cleavage and used for the amplification of target DNA.…”
Section: Discussionmentioning
confidence: 99%
“…This improved the sensitivity and specificity from the source of the detection method (Figure 1) [42]. Conventional nucleic acid amplification methods require at least 1 × 10 3 CFU/mL of colonies as a template to perform normal amplification [43,44], while sample enrichment by ICB in the ICB-LAMP-CRISPR/Cas12a method could reach a detection limit of 8 × 10 0 CFU/mL. For the captured C. jejuni, template DNA was released by direct heating cleavage and used for the amplification of target DNA.…”
Section: Discussionmentioning
confidence: 99%
“…In routine diagnostic settings, real-time quantitative PCR (qPCR) is often used due to increased sensitivity and speed as compared to conventional PCR. Additionally, real-time qPCR allows quantification by the gene copy numbers of the given pathogen or cycle threshold (Ct) values and can therefore also be useful for monitoring the course of infection (Che et al 2019 ). However, it should be kept in mind that detection of DNA does not necessarily indicate that viable pathogens are present, and false-positive results may be obtained after successful treatment (Kuleš et al 2017 ).…”
Section: Commonly Used Diagnostic Methods For Tbds In Human and Veterinary Medicinementioning
confidence: 99%
“…However, since only certain manifestations of Lyme borreliosis are reportable in some, but not all, federal states, this number may be inaccurate (Lohr et al 2015). In contrast, TBE is notifiable in all parts of Germany and annual case numbers ranged between 195 and 584 in the period 2001-2019(Robert Koch-Institut 2020. Less is known regarding other TBDs in Germany, but human cases of neoehrlichiosis (von Loewenich et al 2010) and babesiosis due to B. venatorum (Häselbarth et al 2007) and B. microti (Hildebrandt et al 2007) have been reported during the past decades.…”
Section: Relevant Zoonotic Tbds and Commercial Availability Of Diagnomentioning
confidence: 99%
“…46,47 Additionally, the positive rate of detection is low during the acute phase of infection, making it easy to miss a proper diagnosis. PCR, 48 a genetic testing strategy, has several advantages, including its ability to tolerate internal and external factors that may affect the concentration of genetic testing analytes. This helps overcome the challenges posed by individual differences in detection.…”
Section: 7mentioning
confidence: 99%